Rules of the Port Sunlight Employees' Holiday Club - Leverhulme, William Hesketh Lever, Viscount, 1851-1925 (1909)
1909 1909 1900s 10 pages APPENDIX. xxv. Males rated at over 12/- per week, a deduction of 1 hour's pay. (In the case of a fraction of 1d., a full penny will be deducted.) Males rated at 12/- and under per week, a deduction of 3d. Females, a deduction (at the option of the employee) of 3d. or 6d. On the acceptance by the Company of such form duly signed, such employee shall become a member of the Club, and he or she, whilst remaining a member, shall be bound by and conform to all the rules of the Club from time to time in force. Every person before becoming a member shall be deemed to have had full notice of all the Rules of the Club, and on becoming a member shall be entitled to receive a copy of same on application to the Secretary. 5. Any member objecting to the Company making the aforesaid deduction from his or her weekly earnings in any particular instance, or cancelling or withdrawing his or her authority to the Company to make the same, or ceasing to be an employee of the Company at Port Sunlight, or otherwise ceasing to be eligible for membership under Clause 3, shall forthwith cease to be a member of the Club. 6. No member shall be qualified for a holiday in any year whose membership has not existed continuously for a period commencing before receipt of his or her first payment of wages in the month of October in the previous year, except that every member whose membership has existed continuously for a period commencing before receipt of his or her first payment of wages in the month of January, 1905, shall be qualified for a holiday in that year. 7. No member whose contributions under Clause 4 towards a holiday in any year shall be in arrear shall receive such holiday while such arrears exist, but this rule may, if the Committee so think fit, be waived by them in any case where they are satisfied that the arrears have arisen by reason of the inability of the member to work owing to personal illness or accident. The Company will not agree to make any deduction from wages in respect of arrears. 8. The order in which members receive their holidays shall be entirely in the discretion of the Company, and shall be decided by the Company alone, in such manner and at such time or times as they may think fit. 9. On the receipt by a member of a written notice from the Company of the date of his or her holiday, he or she shall produce the same to the Secretary of the Club or to an Assistant Secretary (if any) for endorsement by him, at such time and place as may from time to time be notified by the Secretary, and thereafter shall have the notice countersigned by his or her Manager or Foreman, whereupon such notice shall entitle him or her, on the day of leaving for such holiday, to withdraw from the Company the amount then standing to his or her credit in respect of the aforesaid deductions, plus allowance for interest thereon as hereinafter mentioned. Any member may also withdraw at any other time (but without any allowance for interest) the amount standing to his or her credit as aforesaid, but in such event such person shall at once cease to be a member of the Club, unless such withdrawal is made with the approval of the Committee, previously notified in writing to the Company by the Secretary; also, any person on ceasing to be a member of the Club for any reason whatever shall be entitled to withdraw the amount (if any) then standing to his or her credit as aforesaid, but without any allowance for interest. 10. The amount standing to the credit of any member as aforesaid shall not be assignable, and if any member shall attempt to assign or charge the same, he or she shall forthwith cease to be a member of the Club. 11. The Company have expressed their intention to allow, as interest, 1d. for every complete sum of 4s. withdrawn after the expiration of the year 1905 by a member about to start on his or her week's holiday. No allowance for interest will be made on any fraction of 4s., nor will any allowance whatsoever for interest be made on any withdrawals in the year 1905 or on any withdrawal at any time by any person other than a member about to start on his or her week's holiday. 12. A meeting of the members of the Club shall be held in the month of January in every year. The first meeting shall be held in the month of January, 1906, and subsequent meetings shall be held in the month of January in every succeeding year. Such meetings shall be called Ordinary General Meetings. All other meetings of the members shall be called Extraordinary General Meetings. The quorum for any General Meeting shall be 25 members personally present, and if no quorum be present at such meeting, the meeting shall stand adjourned until the same hour on the next business day, when the business of the meeting may be proceeded with, notwithstanding that a quorum may not be present. An Extraordinary General Meeting may be called at any time by the Committee, and shall be called within ten days from the receipt at any time of a requisition in writing, signed by 50 or more members, or on the receipt at any time of a requisition in writing signed by the Extraordinary Members hereinafter mentioned, or a majority of them. All General Meetings, as well as all meetings of Committee, shall be held in Port Sunlight. 13. Three clear days' notice of every General Meeting shall be given. It shall not be necessary to specify any business in the notice convening the Ordinary General Meeting in each year, but no business shall be transacted at any Extraordinary General Meeting except that specified in the notice. All notices shall be posted on the notice Boards in the Company's Works, which shall be deemed to be full notice to every member, and no member shall be entitled to any further notice. 14. The Chairman of the Committee shall be entitled to take the chair at every Meeting of Committee and Members; in his absence the members present shall appoint one of their number to be Chairman of the Meeting. All questions arising at any meeting shall be decided by a majority of votes and in case of an equality of votes the Chairman shall have a casting vote. 15. Every member shall have one vote on every question arising at a General Meeting, and such vote can only be given personally. At every General Meeting the members present shall appoint four of their number as scrutineers, whose duty it shall be to count the votes under the direction of the Chairman, and report the result to him, who shall thereupon declare such result, and such declaration shall be final. 36/H24/20